Strategi Pemerintah dalam Menjaga Ketahanan Pangan Melalui Kebijakan Publik - Nabila Zahra; Ropiah Daulay; Ahmad Wahyudi Zein (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
Food security is a crucial aspect of national development that ensures the availability, affordability, and safety of food for all communities. This article examines the Indonesian government's strategies to maintain food security through public policies using a qualitative literature study approach. The study focuses on agricultural infrastructure development, productivity improvement, food diversification, strengthening distribution systems, and empowering communities and farmers. Both central and regional governments play strategic roles in formulating and implementing adaptive policies addressing challenges such as climate change, resource limitations, and food price volatility. Additionally, large budget allocations and innovative financing approaches like green bonds and public-private partnerships are key instruments supporting sustainable food security. The role of regional governments is also vital in regulation, facilitation, and community empowerment to ensure local food security. The findings indicate that integrated public policies and stakeholder synergy effectively enhance national food security comprehensively and sustainably.